Impact of the COVID-19 Pandemic on Religiosity: Evidence from Germany - Eylem Kanol; Ines Michalowski (Journal for the Scientific Study of Religion, 2023)
How does a major external shock that potentially threatens the community and the individual impact religiosity in the context of ongoing secularization? Do individuals in a rich and secularized society such as Germany react to potential community-level (sociotropic) and individual-level (egotropic) threat with heightened religiosity? We estimate multilevel regression models to investigate the impact of sociotropic and egotropic existential security threats associated with the COVID-19 pandemic on individuals' religiosity. Our data come from a rolling cross-sectional online survey conducted in Germany among 7,500 respondents across 13 waves in 2020. Our findings suggest that a global health pandemic such as COVID-19 increases individuals' perception of existential and economic threat, which, in turn, leads to an increase in religiosity. However, this relationship is only true for egotropic existential security threat but not for sociotropic threat. We discuss the theoretical implications of these findings.
Keywords: 320; religiosity; COVID-19; Germany; existential security; economic insecurity